A Draft Genome Resource for Marasmius tenuissimus, an Emerging Causal Agent of Thread Blight Disease in Cacao - Jason Leung; Stephen P. Cohen; Indrani K. Baruah; Shahin S. Ali; Jonathan Shao; Yahaya Bukari; Ishmael Amoako-Attah; Lyndel W. Meinhardt; Bryan A. Bailey (PhytoFrontiers, 2023)
Thread blight disease (TBD) is a serious emerging threat to global cacao production, causing leaf blight symptoms and necrosis in the canopy of infected trees. Though previously thought to be caused primarily by the fungus Marasmiellus scandens, recent work has revealed that a variety of pathogenic Marasmiaceae are responsible for TBD, with Marasmius tenuissimus identified as the dominant causal agent of TBD in Ghanaian cacao plantations. M. tenuissimus has also been reported in remote organic cacao plantations in the Amazonas Department of Peru, infecting 90 to 100% of the trees surveyed. Here, we have assembled and annotated the nuclear genome of M. tenuissimus isolate GH-37. This resource is a first attempt at a high-quality draft genome utilizing both second- and third-generation sequencing for M. tenuissimus and extends the current understanding of the evolution, ecology, and virulence of this pathogen. [Figure: see text] Copyright © 2023 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.